2020
DOI: 10.1186/s13002-020-00363-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ethnopharmacological documentation and molecular confirmation of medicinal plants used by the Manobo tribe of Agusan del Sur, Philippines

Abstract: Background: The Philippines is renowned as one of the species-rich countries and culturally megadiverse in ethnicity around the globe. However, ethnopharmacological studies in the Philippines are still limited especially in the most numerous ethnic tribal populations in the southern part of the archipelago. This present study aims to document the traditional practices, medicinal plant use, and knowledge; to determine the relative importance, consensus, and the extent of all medicinal plants used; and to integr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
64
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 72 publications
(94 reference statements)
15
64
1
Order By: Relevance
“…Similar results were found by Dapar et al [69] for gender and healer categories. However, the latter authors found that age, education and marital status influenced respondent's medicinal knowledge whereas there was no influence of their residence location.…”
Section: Traditional Medicinal Knowledge Among Social and Ethnic Groupssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were found by Dapar et al [69] for gender and healer categories. However, the latter authors found that age, education and marital status influenced respondent's medicinal knowledge whereas there was no influence of their residence location.…”
Section: Traditional Medicinal Knowledge Among Social and Ethnic Groupssupporting
confidence: 91%
“…Similar findings were obtained by Dapar et al [69] for men, adults and elderly, married and secondary-school-educated therapists as well as by Sanga [70] for therapists living in urban areas. Nzuki [10], however, found that in Mbanza-Ngungu, rural therapists may have more knowledge than urban therapists.…”
Section: Traditional Medicinal Knowledge Among Social and Ethnic Groupssupporting
confidence: 90%
“…Similar results were found by Dapar et al [64] for gender and categories of healers. In contrast, he found opposite results…”
Section: Traditional Medicinal Knowledge Among Social Groupssupporting
confidence: 91%
“…Similar findings were obtained by Dapar et al [64] for men, adults and elderly, married and secondary school therapists as well as by Sanga [65] for therapists living in urban areas, but are contrary to findings of Nzuki [10] who estimated that in Mbanza-Ngungu, rural therapists may have more knowledge than urban's. This difference may be due to the fact that Nzuki's observation is based on the comparison (%) between urban and rural healers who use "more than 10 medicinal plants" but not on the average number of plants used by each.…”
Section: Traditional Medicinal Knowledge Among Social Groupssupporting
confidence: 86%
“…Both leaves and roots are chewed and swallowed to lessen dizziness and sore throat among the Ayta community of Bataan, Philippines (Tantengco et al 2018). Dapar et al (2020) documented the ethnopharmacological uses of M. philippica among the Manobo tribe in Agusan del Sur, as a remedy for jaundice, colds, dysentery, stomachache, fever, and snakebite. They drink 2-3 glasses of decocted bark and leaves.…”
Section: Local Medicinal Usesmentioning
confidence: 99%